(untitled) (International Journal of Food and Nutritional Sciences, 2022)
For the purpose of the present study, the variables of Self-concept and Adjustment among Secondary Schools in Assam. The main aim of the present study is to investigate the significant difference between Self-concept and Adjustment among Secondary Schools in Assam